War and criminal law policy of Ukraine: challenges and responses (Law and Safety, 2022)
The article is devoted to the characteristics of the main challenges of the war for the development of Ukrainian society and the state and responses to them in the field of criminal law policy formation and implementation. The purpose of the article is to provide a systemic characterization of the changes that have taken place in the Criminal Code of Ukraine since February 24, 2022 and are aimed at responding to challenges related to martial law, as well as determining their necessity, sufficiency, and adequacy.The empirical basis of the study is made up of the materials of 225 court verdicts for the commission of criminal offenses provided for by Articles 111, 111-1, 111-2, 114-2, 436-2, 438 of the Criminal Code of Ukraine, as well as the results of expert assessments and surveys of 92 employees of pre-trial investigation bodies of the National of the police, 35 employees of the prosecutor’s office, 30 investigators of the Security Service of Ukraine in Kharkiv, Odesa and Zaporizhzhia regions. The analysis of these sources made it possible to identify and describe the existing problems of criminal law regulation of social relations in a number of spheres, which have been exposed to the greatest negative influence since the beginning of the full-scale war of the Russian Federation against Ukraine.A description and explanation of the main and indirect threats associated with the full-scale armed aggression of the Russian Federation against Ukraine is provided. The changes in the law on criminal liability, which occurred as a reaction to the specified threats in the form of criminalization of socially dangerous acts, as well as in the practice of applying criminal law norms on collaborationism, aiding the aggressor state, justification, denial of armed aggression against Ukraine, war crimes, etc., are analyzed. Their shortcomings and defects are identified, proposals are formulated for their elimination through improvement both at the law-making and law-enforcement levels. The need for Ukraine to ratify the Rome Statute of the International Criminal Court and the Kampala annexes to it is emphasized. Equally significant is the improvement of domestic legislation and the practice of its application in relation to countering collaborationism, aiding the aggressor state, as well as war crimes, crimes of aggression, and crimes against humanity.The inadequacy of the application of norms on war crimes in those cases in which terrorism takes place has been established at the level of a separate scientific and law-enforcement problem. The possibility of the coexistence of the phenomena of terrorism and aggressive war, the presence of signs of war crimes and terrorist acts in the actions of combatants has been proven. The key factor in distinguishing these phenomena should not be the international legal status of the guilty person as a combatant, but the content of the subjective side of the composition of the criminal offense with a significant coincidence of the signs of the objective side of war crimes and terrorist acts.
Keywords: war; criminal law policy; challenge; response; aggression; war crime; crime against humanity; collaborationism.